2007
DOI: 10.1177/1420326x07080855
|View full text |Cite
|
Sign up to set email alerts
|

Biological Hazards in Tannery Workers

Abstract: A total of 431 workers from 14 leather factories located in the Tuzla Organized Industry Region, Istanbul were involved in the study. Subjects were interviewed and examined individually with regard to asthma symptoms. Physical examinations were undertaken and respiratory function measured by spirometer. Moreover, the atmosphere of the working areas in the factories was assessed microbiologically. The fungal genera most often detected were Penicillium spp., followed by Aspergillus spp., Alternaria spp., Scopula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
(15 reference statements)
1
9
0
Order By: Relevance
“…Others studies have reported airborne fungi are of greater significance than bacteria as causes of allergic disorders such as rhinitis or asthma [28] . Our findings indicate that the Enterobacteriaceae family represents 57% of all identified bacteria in oropharyngeal mucosa of tanners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others studies have reported airborne fungi are of greater significance than bacteria as causes of allergic disorders such as rhinitis or asthma [28] . Our findings indicate that the Enterobacteriaceae family represents 57% of all identified bacteria in oropharyngeal mucosa of tanners.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the poor air quality in the working environment of the tanneries and because many of these microorganisms can be acquired by the workers, either by inhalation, ingestion, or other means, some of the identified bacteria, in the indoor environment of tanneries, belonged to the following families: Bacillaceae, Corynebacteriaceae, Enterobacteriaceae, Moraxellaceae, Nocardiopsaceae, Pseudomonadaceae, and Staphylococcaceae. In addition, fungi genuses were also identified by microscopy and these included Aspergillus and Penicillium, which are considered the airborne allergenic fungi most significant and found to be associated with adverse effects on human and animal health [28] . Additionally, yeasts identified were C. krusei and C. glabrata, both of which have been associated with adverse health effects in individuals with compromised immune systems [13,29] .…”
Section: Discussionmentioning
confidence: 99%
“…These health-related issues were strongly correlated with the mould present in the tannery environment. 67…”
Section: Discussionmentioning
confidence: 99%
“…Fungi have also been confirmed to be natural inhabitants of hides/skins. Fungi species can tolerate high NaCI concentrations of 20-30% (w/v) [17]. This is a higher concentration than that tolerated by bacteria.…”
Section: Microbes Reported In Animal Skins and Leather Productsmentioning
confidence: 99%
“…and Cladosporium spp. were isolated from salted sheepskins [17]. From the curing premises, the raw hides and skins are taken to tanneries for processing.…”
Section: Microbes Reported In Animal Skins and Leather Productsmentioning
confidence: 99%